Development of the Japanese version of Staff Attitude to Coercion Scale - Fukasawa, Maiko; Miyake, Michi; Kikkawa, Takahiro; Sueyasu, Tamio (Frontiers in Psychiatry, 2022)
Background: An important factor in proceeding the efforts to reduce coercion in psychiatry is the attitudes of clinical staff toward its use. We aimed to develop the Japanese version of the Staff Attitude to Coercion Scale (SACS) and clarify its psychometric properties. Methods: After the translation and back-translation of the SACS, which includes 15 items consisting of three subscales, we conducted an anonymous self-administered questionnaire survey of clinical staffs working in 17 wards in two psychiatric hospitals. We administered the second survey to some of the participants to confirm the test-retest reliability. Additionally, we obtained information regarding the 17 wards from the institutions. Internal consistency was assessed using Cronbach’s alpha coefficients. Test-retest reliability was assessed using intraclass correlation coefficients (ICC). Structural validity was examined using confirmatory factor analysis (CFA) and exploratory factor analysis (EFA). For construct validity, the correlation of the SACS score within wards and its association with the actual use of seclusion/restraints were explored using multilevel multivariate linear regression analyses. Results: We used 261 (67.1%) responses, 35 responses of which were also used to examine test-retest reliability. Cronbach’s alpha coefficients (0.761) and ICC (0.738) indicated good reliability. The results of CFA based on the original three-dimensional structure did not indicate a good fit (CFA=0.830, RMSEA=0.088). EFA suggested a four-factor structure, two of which were almost consistent with the original two subscales. The correlation of the SACS score within wards was confirmed while a positive association with the actual use of seclusion/restraints was not identified. Conclusions: While the original three-dimensional structure was not replicated, construct validity was partially confirmed. Reliability of the total scale was good. In Japan, although using the subscales was not recommended, using the total scale of SACS seemed acceptable.